Performance evaluation of phase encoding schemes in multi-user networks - Thio, T. H. G.; Go, Y. I. (IET, 2014)
This paper presents a performance evaluation of different encoding schemes based on phase-encoding techniques. Conventional multiplexing techniques and multiple-access schemes are reviewed, and the transmitter and receiver architectures are outlined. Different encoding schemes are developed based on the standard spread-spectrum technique and the performance of each scheme is tested in an optical network simulated using real field configurations. The encoding stage is performed in the optical domain, and different fiber Bragg grating configurations are investigated. An eight-user system model is developed and the performance is examined under a wide range of different modulation techniques including standard modulation techniques such as amplitude shift keying (ASK) and on-off keying (OOK), as well as differential techniques such as differential phase shift keying (DPSK) and differential quadrature phase shift keying (DQPSK). The bit-error rate (BER) performance of the systems is examined at different transmission distances and the required signal-to-noise ratio (SNR) is measured. The propagation loss is examined by measuring the system performance before transmission from each user. This paper demonstrates that optimal system performance depends not only on the code correlation properties, but also on the configuration of the encoder as well as the compatibility of the modulation techniques applied.